2020
DOI: 10.3390/app10030988
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Growth Conditions may Regulate Resistance of Listeria monocytogenes Biofilms to Benzalkonium Chloride

Abstract: Listeria monocytogenes is one of the main foodborne pathogens. The formation of biofilms by L. monocytogenes contributes to its resistance to disinfectants, which represents a serious risk for food production plants. The aim of this study was to compare the effect of sub-inhibitory concentrations of benzalkonium chloride (BAC) (1.25 or 2.5 mg/L) on biofilm production and on biofilm reduction after exposure to an inhibitory concentration of BAC (1280 mg/L) in two isogenic L. monocytogenes strains: the BAC-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Only a few studies investigated the effect of BKC exposure at sub‐MIC concentration on biofilm formation and evidence from different studies is at time contradictory. BKC was shown to induce biofilm formation in Staphylococcus epidermidis (Houari & Di Martino, 2007 ), K. pneumoniae (Elekhnawy et al, 2021 ) and L. monocytogenes (Bonneville et al, 2020 ; Piercey et al, 2017 ), or to increase biofilm biomass in E. coli (Machado et al, 2012 ; Yu et al, 2021 ), P. aeruginosa (Machado et al, 2012 ) and A. baumannii (Rajamohan et al, 2009 ). Others have however shown that BKC exposure decreases bacterial ability to form biofilms in S. aureus (Buzón‐Durán et al, 2017 ) and in L. monocytogenes (Ortiz et al, 2014a ).…”
Section: Benzalkonium Chloride and Bacterial ‘Resistance’mentioning
confidence: 99%
“…Only a few studies investigated the effect of BKC exposure at sub‐MIC concentration on biofilm formation and evidence from different studies is at time contradictory. BKC was shown to induce biofilm formation in Staphylococcus epidermidis (Houari & Di Martino, 2007 ), K. pneumoniae (Elekhnawy et al, 2021 ) and L. monocytogenes (Bonneville et al, 2020 ; Piercey et al, 2017 ), or to increase biofilm biomass in E. coli (Machado et al, 2012 ; Yu et al, 2021 ), P. aeruginosa (Machado et al, 2012 ) and A. baumannii (Rajamohan et al, 2009 ). Others have however shown that BKC exposure decreases bacterial ability to form biofilms in S. aureus (Buzón‐Durán et al, 2017 ) and in L. monocytogenes (Ortiz et al, 2014a ).…”
Section: Benzalkonium Chloride and Bacterial ‘Resistance’mentioning
confidence: 99%
“…Moreover, it keeps the microorganisms in tight contact with each other to facilitate quorum sensing (QS), and it contains genetic information as well, e.g., the extracellular DNA [5,7]. Pathogenic bacteria organised in biofilms are considered to be a major health concern [8][9][10][11][12]. Bacteria living in a biofilm are much more resistant to antibiotics than their planktonic form, leading to persistent infections [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They have been found in hospital settings, for instance on medical devices or implants (valves, stents, catheters), leading to infections and death [15]. Within the food chain and industry, they are responsible for contamination and cross-contamination of food products and therefore lead to outbreaks of foodborne diseases [11]. Moreover, their ubiquity on common surfaces in, e.g., kitchens (kitchen worktops, refrigerators), bathrooms (sinks, toilets) and offices (desks, keyboards), requires devising new disinfection strategies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations